2016
DOI: 10.1186/s12917-016-0741-5
|View full text |Cite
|
Sign up to set email alerts
|

A 2015 outbreak of Getah virus infection occurring among Japanese racehorses sequentially to an outbreak in 2014 at the same site

Abstract: BackgroundAs we reported previously, Getah virus infection occurred in horses at the Miho training center of the Japan Racing Association in 2014. This was the first outbreak after a 31-year absence in Japan. Here, we report a recurrent outbreak of Getah virus infection in 2015, sequential to the 2014 one at the same site, and we summarize its epizootiological aspects to estimate the risk of further outbreaks in upcoming years.ResultsThe outbreak occurred from mid-August to late October 2015, affecting 30 race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Several GETV outbreaks have occurred in horses and swine in Japan (Bannai et al 2016), India (Broen and Timoney 1998), and China (Yang et al 2018). The results of this study revealed that there is a high titer of the GETV neutralizing antibody in many domestic animals in Yunnan Province, which suggests that GETV may cause infections in domestic animals in the local area.…”
Section: Fig 1 Serological Survey Of Getv In Domestic Animalsmentioning
confidence: 64%
See 1 more Smart Citation
“…Several GETV outbreaks have occurred in horses and swine in Japan (Bannai et al 2016), India (Broen and Timoney 1998), and China (Yang et al 2018). The results of this study revealed that there is a high titer of the GETV neutralizing antibody in many domestic animals in Yunnan Province, which suggests that GETV may cause infections in domestic animals in the local area.…”
Section: Fig 1 Serological Survey Of Getv In Domestic Animalsmentioning
confidence: 64%
“…In 1978, the first outbreak of GETV infection in horses was reported in Japan, and nearly 40% of the local horse population became infected. In 2012, prevalent GETV infection in horses occurred again in Japan (Bannai et al 2016). In the 1990s, an outbreak of GETV occurred among horses in India, and the associated morbidity reached 30% (Broen and Timoney 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The first epizootic GETV infection occurred among racehorses in Japan in 1978 (Kamada et al., ). Subsequently, outbreaks of GETV infection have occurred among horses in 1979, 1983, 2014 and 2015 in Japan (Bannai et al., ; Nemoto et al., ; Sentsui & Kono, ; Sugiura et al., ) and in 1990 in India (Brown & Timoney, ). In pigs, sporadic cases of GETV infection were reported in the 1980s in Japan (Shibata, Hatano, Nishimura, Suzuki, & Inaba, ; Yago, Hagiwara, Kawamura, & Narita, ); a recent seroepizootiologic investigation found GETV circulating in south Ibaraki and north Chiba in Japan, and this circulation was concomitant with the outbreaks in racehorses (Bannai et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of GETV has been confirmed in mainland China, Japan, Korea, and Taiwan (229,230). Outbreaks of GETV infection have occurred among Japanese racehorses (231,232). It is known that GETV also infects cattle, although there is no evidence of illness in the infected cattle (226,233,234).…”
Section: Other Arbovirusesmentioning
confidence: 99%